Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas - García-Gómez, Arturo; Palacios-Vargas, José G. (Zootaxa, 2019)
Willemia panamaensis sp. nov. from Panama is described and illustrated. It is characterised by the presence of sensilla I (S2) and i1 (S9) on antennal segment IV, nine vesicles in the postantennal organ, and having dorsal setae and sensilla on abdominal segments V and VI twice as long than on segments I and II. A dichotomous key to species recorded from the Americas is provided. Reference is given to the DNA barcoding sequences of the new species.